Legal issues in mapping traditional knowledge: Digital cartography in the canadian north - Scassa, T. (Teresa); Engler, N.J. (Nate J.); Taylor, D.R. (Fraser) (The Cartographic Journal, 2015)
Digital cartography offers great potential for mapping the traditional knowledge of indigenous communities. This is particularly so because of the close relationship between such knowledge and traditional lands. Yet the mapping of traditional knowledge also raises distinct legal and ethical considerations which should be at the forefront in the design and implementation of indigenous digital cartography projects. This paper examines these considerations through the lens of digital atlases jointly created by Inuit communities and Carleton University’s Geomatics and Cartographic Research Centre (GCRC).